Potent In-vitro Anti-plasmodium Activity of Hydromethanolic and Aqueous Extracts of Xanthium strumarium - Hyacinth Highland,; Simi Mathew,; Dhara Jani,; Linz-Buoy George, (International Journal of Phytomedicine, 2015)
Malaria is known to account for a large fraction of the mortality in most tropical countries. In recent times the increase in new, drug-resistant strains of the Plasmodium parasite has triggered the search for novel, effective, anti-plasmodial agents, with minimal side effects. Hence, herbal extracts, rich in potent phytochemicals, are currently proving effective in the combat against malaria and its varied forms. In the present study therefore, extracts of bur of Xanthium strumarium were analyzed to determine the major secondary metabolites and active phytocomponents. The anti-malarial efficacy of these extracts were then tested in-vitro on MRC-2 and 3D7 P. falciparum strains. The effect on cultures of infected RBC treated with test extract for 24 hours were compared with normal RBC alone, Plasmodia Infected RBC, Synchronized infected RBC and scored according to the WHO guidelines. The IC50 values was derived and the study revealed that the Hydromethanolic and Aqueous extracts proved most potent in containing the parasite proliferation. This was concomitant with the phytochemical data which showed that these extracts were rich in active phytoconstituents, and hence these extracts show promise as effective anti-plasmodial agents even against the drug resistant strains.